Global, regional, and national temporal trends in mortality and disability-adjusted life years for cardiovascular disease attributable to low temperature during 1990–2019: an age-period-cohort analysis of the global burden of disease 2019 study - Li, Xiaofei; Liu, Zeye; Xie, Jing; Shao, Hua; Xia, Ruibing; Li, Yakun; Liu, Yun; Fan, Xiaohan (Frontiers in Public Health, 2024)
Background Few studies have focused on the region-specific relationship between cardiovascular disease (CVD) and low temperature worldwide. Objective We aimed to provide an overview of trends in mortality and disability-adjusted life years (DALYs) for CVD and its subtypes attributable to low temperature over the past 30 years in 204 countries and regions, along with the associations of these trends with age, period, and birth cohorts. Methods Data on the estimated burden of CVDs (including ischemic heart disease, hypertensive heart disease, and stroke) attributable to low temperature were obtained from the Global Burden of Disease Study 2019. We utilized an age-period-cohort model to estimate overall annual percentage changes in mortality (net drifts), annual percentage changes from 15 19 to 81 85 years (local drifts), and period and cohort relative risk (period/cohort effects) between 1990 and 2019. Results Among noncommunicable diseases, CVDs had the highest mortality rate and DALY loss attributable to low temperature worldwide and has increased from 65.7 to 67.3%, which is mainly attributed to the increase in East Asia and Pacific region. In terms of the level of economic and social development, an inverted U-shape was found in the age-standardized mortality rates (ASMR) due to low-temperature across different sociodemographic indices (SDI) regions. Both high CVD mortality (19.45, 95% CI [14.54, 24.17%]) and a decreasing mortality rate related to low temperature (from 1990 to 2019, net drift, −3.25% [−3.76, 2.73%] per year) was found in high SDI countries or territories, with opposite outcome found in low SDIs regions. The older adults (70+) and men share the highest rate of CVD ASMR and DALY attributed to low temperature across all regions, especially in North America and Europe and Central Asia. Conclusion Mortality and DALY loss from CVD attributable to low temperature showed an overall decreasing trend globally except for East Asia and Pacific region. SDI, sex, age and geographic location contributed to the diversity of the CVD disease burden associated with low temperature worldwide. More attention should be given to the older adults, men, and low SDI regions.